A novel experimental method to study metal vapor condensation/oxidation: Mg in CO and CO2 at reduced pressures. (1st December 2016) - Hischier, Illias; Chubukov, Boris A.; Wallace, Mark A.; Fisher, Richard P.; Palumbo, Aaron W.; Rowe, Scott C.; Groehn, Arto J.; Weimer, Alan W.
Graphical abstract: Highlights: An experimental method is presented to study oxidation/condensation of metal vapor. Mg(g) and CO coexist in a metastable phase. At low CO partial pressures Mg(g) can heterogeneously condense at high purity. Abstract: A novel method is presented to study magnesium metal vapor condensation/oxidation in CO and CO2 atmosphere at reduced pressures. Mg(s) was evaporated and mixed with an equimolar amount of CO or CO2 at 1000 °C after which the gaseous mixture flowed through an air cooled tubular condenser. Measurements of the axial temperature profile, calculation of partial pressures and analysis of deposits within the condenser allowed for identification of deposition/condensation onset temperatures, supersaturation ratio and reaction mechanism. In the presence of CO2, rapid oxidation of Mg(g) has been observed. In the presence of CO, no Mg(g) oxidation was found above 950 °C. Mg(g) oxidation observed at lower temperatures is believed to be initiated by CO disproportionation. The proposed mechanism is able to explain the increase in Mg metal yield with decreasing CO partial pressure. At a CO partial pressure <3 mbar, high Mg metal mass yields of >90 w% were found. The presented method is applicable to the study of a variety of metal vapor/oxidizer combinations e.g. of interest in metal and solar fuel production.